The Effect of Metacognitive Ability on Learning Outcomes of Geography Education Students - Faisal Arif Setiawan; Deasy Arisanty; Karunia Puji Hastuti; Akhmad Munaya Rahman (Universitas Muhammadiyah Surakarta, 2020)
The objective of this study was to analyze the effect of metacognitive ability to improve the geography learning outcomes. This research is expo facto with a quantitative approach. Data was collected from 55 students from the geography education department. Data collection methods used in this study was questionnaires and documentation. The results showed that the metacognitive abilities of students had an average value of 44.57 or that metacognitive abilities were an insufficient category. There was a significant influence of metacognitive abilities on student learning outcomes as evidenced by t count = 6.508 > t table = 1.674. The contribution of the influence of metacognitive abilities on biogeography learning outcomes was equal to 0.444 or 44.4%, while the remainder of 66.6% was influenced by other factors.